State of the struggle : report on the battle against global terrorism / Lee Hamilton ... [et al.] ; edited by Justine A. Rosenthal. - Hamilton, Lee; Rosenthal, Justine A. (Council on Global Terrorism, 2006)
"Assesses the West's progress across a wide array of counterterrorism imperatives. From ethical questions of balancing security and core values to the problems of creating viable counterterrorism coalitions to the likelihood of biological, chemical, and nuclear weapons, report examines a wide swath of issues necessary to create workable counterterrorism strategies"--Provided by publisher